Evaluación docente para la mejora continua en el cantón Saquisilí - Landeta Chipantasi, Segundo Antonio (2017)
The project was an exploratory and descriptive research, so that the primary objective was to diagnose the current scenario of teacher evaluation, to describe the problem of the evaluation process, also to know the reality of the teachers evaluated. We investigated the factors of teacher evaluation as a whole, that is, sought the characteristics, purpose, advantages, disadvantages and the debate that has generated in society; to effect a field investigation. Also in this project was used the method of observation, when applying the techniques and instruments of research, also used the analytical method when analyzing and interpreting the results, finally used the synthetic method to draw conclusions and recommendations. In making this examination, real information was obtained from the teacher evaluation, and it was verified that this problem is discussed in similar research, in the case of the present project was executed to know the evaluation system is working. It was also examined to know the criteria of teachers versus the assessment of professional performance. Evidently, this exploration helped to discover the deficiencies and strengths of the evaluation system and of the evaluated teachers, besides contributing with primary information to the project that will realize the Cotopaxi Technical University....